Fieldworker and the field problems and challenges in sociological investigation - Ramaswamy E A; Shah A M; Srinivas M N (Oxford OUP, 2002)
Description This is a paperback of a 1979 hardback which broke new ground in social investigation. There have, since, been other books on the experience of fieldwork, but this remains a much cited work. The eighteen essays in the volume describe the expe
Keywords: Sociology-research